Development of Student Worksheets for Economics Subjects Based on Learning By Doing for Class X Students - Suratno, Suratno; Budiyono, Herman; Budi, Eka (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2019)
This research aims to (1) develop student worksheets for economics subjects based on learning by doing for class learn using student worksheets developed. The method used in this development research is the 4-D (Four D) Research and Development (R&D) model method. The instruments used were observation sheets and questionnaires using a Likert scale as well as cognitive questions in the form of multiple choices. The resulting product is validated by a team of experts and tested on small and large groups.The resulting product is a student worksheet based on learning by doing which was developed using a 4-D model and validated by a team of experts with 1 revision. The validation results obtained by material experts were: 86.40% (very feasible), media experts: 80.00% (feasible), teacher response: 90.40% (very feasible), so that the student worksheets developed were suitable for testing. The results of the small group trial obtained the percentage: 98.00% (very interesting) and the large group: 98.44% (very interesting). From the results of the pre-test and post-test, the values (g) were obtained: low: 5 people, medium: 25 people and high: 2 people. This shows that the student worksheets developed are of good quality with 100% classical completeness. So it can be concluded that student worksheets based on learning by doing in economics subjects are declared very feasible, very interesting and effective for use by teachers and students of class.